NFC Model: A new paradigm for sustainable agriculture - Maring, Kanshouwa Modunshim (Indian Farming, 2024)
In pursuit of sustainable agriculture, a revolutionary model has emerged, one that places primary importance on the symbiotic connection between nature, farmers, and consumers. This groundbreaking model, named ’Nature-Farmer-Consumer’ (NFC) model, promotes a drastic shift from conventional, linear supply chain frameworks and upholds the idea that consumers are not passive observers but active influencers in the journey for sustainable transformation within agri-food systems.